Situational Crisis Communication Kementerian Komunikasi dan Digital dalam Menangani Kasus Kebocoran Data PDNS di Era Digital - Faizal, Khansa Aulia; Masitoh, Siti (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
In the rapidly evolving digital era, information technology presents both opportunities and challenges, particularly in the context of data security. This study focuses on the role of public relations at the Ministry of Communication and Digital (Kemkomdigi) in managing crisis communications arising from the Temporary National Data Center (PDNS) data leak incident. This case attracted public attention because it involved a ransomware cyberattack that significantly impacted more than 210 government agencies. This situation demands an effective, swift, and transparent communication strategy to maintain public trust in government institutions. This study used a qualitative approach with a case study method. Data were collected through observation, documentation, and in-depth interviews with the Kemkomdigi Public Relations Bureau. Data analysis was conducted using the Miles and Huberman interactive model, encompassing data reduction, data presentation, and conclusion drawing. The results show that Kemkomdigi did not employ denial or diminish strategies. Instead, they emphasized rebuilding and bolstering strategies as proposed in Situational Crisis Communication Theory (SCCT). The implementation of these strategies is evident in official apologies, open clarifications, consistent digital information delivery, and strengthening the institutional narrative through press conferences and official communication channels. Thus, this study concludes that appropriate crisis communication strategies contribute significantly to maintaining the government's reputation and credibility in the digital era.